Urgensi Sistem Penjaminan Mutu Internal Terhadap Peningkatan Mutu Perguruan Tinggi - Muh. Fitrah; Ruslan; Hendra (UHN IGB Sugriwa Denpasar, 2018)
One of the effects of globalization is the increase of the opportunity of work but this is accompanied by the strict competition in getting job caused by globalization so the implementation system of university should continually be able to anticipate those dynamic changes that the alumnus has the high competition level. This condition underlines the urgency of system implementation of internal quality guarantee. System implementation of internal quality guarantee was made as the basis control management of the high education quality with national standard. The process of system implementation of internal quality guarantee was not far from quality, target of education implementation quality, and all documentations of quality that mus be socialized elements of academic and institution leader to implement optimally because the important values of effort from system of internal quality guarantee if the discovery gotten, was continued by planning and application of programs for future fixes. There were some crucial urgencies gotten by university in evaluation that was done by system of internal quality guarantee, university should; 1) able to identify power and weakness as the basis of arrangement of continue plan of development. 1) able to learn the opportunity to develop the quality of education, score the success of development effort, and do adaptation of programs; 3) able to know the level of performance success based on Standard, and 4) able to supply the valid report to holder of interest about progress and result-raised.